2019
DOI: 10.1039/c9sc00658c
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic interaction between neighboring platinum and ruthenium monomers boosts CO oxidation

Abstract: The synergetic effect between neighboring Pt and Ru monomers supported on N vacancy-rich g-C3N4 promotes the catalytic CO oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
110
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(113 citation statements)
references
References 32 publications
2
110
0
1
Order By: Relevance
“…In addition to the electrocatalytic reactions mentioned above, SACs have also been reported to be used in other catalytic reactions, including NRR, WGSR, methane reforming, methanol steam reforming, CO oxidation, benzene oxidation, acetylene hydrogenation, and so on. Shan et al reported an atomically dispersed Rh on the zeolite (Rh/ZSM‐5) catalyst, which can convert methane into methanol or acetic acid in liquid phase mild oxidation at 150 °C.…”
Section: Recent Advances Of Densely Populated Sacs In Catalytic Applimentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the electrocatalytic reactions mentioned above, SACs have also been reported to be used in other catalytic reactions, including NRR, WGSR, methane reforming, methanol steam reforming, CO oxidation, benzene oxidation, acetylene hydrogenation, and so on. Shan et al reported an atomically dispersed Rh on the zeolite (Rh/ZSM‐5) catalyst, which can convert methane into methanol or acetic acid in liquid phase mild oxidation at 150 °C.…”
Section: Recent Advances Of Densely Populated Sacs In Catalytic Applimentioning
confidence: 99%
“…The use of a support with high specific surface area is another efficient way to prepare SACs with high mass loading, since the strong electronic or covalent bond between the metal atom and support could prevent the aggregation of high surface energy single atoms. In addition, reasonable design of the atomic structure between the single atoms and substrate by tuning the metal‐support interaction can improve the intrinsic activity of the catalysts …”
Section: Introductionmentioning
confidence: 99%
“…At the moment, although the adsorption of Na 2 SiO 3 species has been considerably investigated, 29,[32][33][34][35] very few studies have been conducted on the Na 2 CO 3 /Na 2 SiO 3 system in otation 17,28,31,36 and the synergistic effects exhibited by this reagent combination are still poorly understood. Some authors have successfully investigated surface reactivity and synergistic adsorptions/ reactions by Fourier transform infrared spectroscopy (FTIR), [37][38][39][40] by X-ray photoelectron spectroscopy (XPS), [41][42][43] and by ab initio molecular dynamics (AIMD) 37,[44][45][46] with couplings between the above-mentioned techniques. In the present study, we use a combination of diffuse reectance infrared Fourier transform spectroscopy (DRIFTS), XPS, and AIMD simulations to gain an understanding of the molecular mechanisms involved in the Na 2 SiO 3 adsorption onto bare surfaces and onto surfaces prior treated with Na 2 CO 3 .…”
mentioning
confidence: 99%
“…Herein, the * indicates adsorbed intermediates. In O* and OOH* configuration (Figure f and g), the electrons (sky blue region) can be effectively aggregated between the Co−O bond or O−O bond, which contributes to the activation of a transition state . The Co atom of V Zn ‐ZNCO bound to O was without an external potential at the first step: O 2 (g) + 1/2 H 2 → OOH* decline in free energy by −1.96 eV (ZNCO: −2.11).…”
Section: Resultsmentioning
confidence: 99%